Pembuatan Bioetanol Dari Ampas Sagu Menggunakan Proses Hidrolisis Dan Fermentasi Menggunakan Asam Sulfat Sebagai Katalis - Dirgantara, Doni Ari; Chairul, Chairul; Zultiniar, Zultiniar (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2021)
Bioethanol is one of the alternative energy substitutes for petroleum. the wasted of sago can be used for bioethanol production. The main component of sago is used for the production of bioethanol is lignocellulose which consist of cellulose, hemicellulose and lignin. Ethanol is made by hydrolisiys and fermentation with the help of an acid catalyst and saccharomyces cerevisiae. This study aims to exploit the potential contained in sago waste as a producer of bioethanol by using the hydrolysis process method acid and time of the hydrolysis process, knowing the amount of sugar content resulting from the acid hydrolysis process and the time of the hydrolysis process, Knowing the ethanol content formed from the time variation in the fermentation process. The variables used are sulfuric acid concentration, hydrolysis time and also the time when fermentation. this research starts with the pre treatment of sago pulp, then hidrolysis with, with variation 1n, 2n, 3n in 145 degree during 20 minutes, 30 minutes, minutes, 40 minutes and 50 minutes. Then the results of hydrolysis fermented using sacchaomces cerevisiae. The fermentation process lasted for 24 hours, 48 hours 72 hours, 96 hours, and 120 hours. The results showed that the largest sugar concentration was obtained during concentration of H2SO4 3 N with time 50 minutes amounting to 25,08 g/L the greatest bioethanol content and levels are obtained from the fermentation during 96 hours is 4,751 g/L or 15 %. Keywords : bioethanol, fermentation, hydrolisis, sago pulp, pre-treatment